Priority setting: women’s health topics in multiple sclerosis - Ross, Lindsay; Finlayson, Marcia; Amato, Maria Pia; Cohen, Jeffrey Alan; Hellwig, Kerstin; Tintore, Mar; Vukusic, Sandra; Salter, Amber; Marrie, Ruth Ann (Frontiers in Neurology, 2024)
Background A scoping review found that most studies on women’s health in multiple sclerosis (MS) focused on pregnancy, fetal/neonatal outcomes and sexual dysfunction. Few studies addressed menopause, contraception, gynecologic cancers/cancer screening. However, the perceived relative importance of these knowledge gaps to people living with MS and other partners is unknown. We engaged a range of partners, including people living with MS, health care providers, researchers, and patient advocacy groups, to set priorities for future research in women’s health in MS. Methods We employed a three-step global engagement process. First, we identified which broad research topics relevant to women’s health in MS were of highest priority using two surveys. Second, we developed specific research questions within these topics using focus groups. Finally, we prioritized the research questions with a third survey. Results Overall, 5,266 individuals responded to the initial surveys [n = 1,430 global survey, mean (SD) age 50.0 (12.6), all continents; n = 3,836 North American Research Committee on Multiple Sclerosis survey, mean (SD) age 64.8 (9.6), United States]. Menopause, sexual dysfunction, pregnancy, gynecologic cancer/cancer screening, hormones and parenthood were identified as the most important topics. Focus groups generated 80 potential research questions related to these topics. In the final survey 712 individuals prioritized these questions. The highest priority questions in each research topic were: (i) How do perimenopause and menopause affect disease activity, course, response to disease-modifying treatment and quality of life in MS; (ii) What are the most effective strategies for managing issues around sexual intimacy, including related to low sexual desire, changes in physical function, and MS symptoms; (iii) Are there long-term effects of disease-modifying therapies on the children of persons with MS; (iv) What are the short and long-term effects of disease-modifying drugs on gynecologic cancer risk, particularly for high efficacy disease-modifying drugs and hematopoietic stem cell transplantation; (v) Are there hormone related treatments that can stabilize fluctuations in MS symptoms; and (vi) How does MS fatigue impact parenting strategies. Conclusion Priorities for research relating to women’s health issues for persons with MS have been delineated using a collaborative process with key partners. Alignment of future research with these priorities should be monitored.